2015
DOI: 10.1007/s10459-015-9618-9
|View full text |Cite
|
Sign up to set email alerts
|

Academic performance and perception of learning following a peer coaching teaching and assessment strategy

Abstract: Peer coaching has been associated with positive effects on learning. Specifically, these associations have been explored in complex healthcare professions. A social theory of learning has been proposed as a key component of the utility of peer coaching. Further, within the peer coaching model, assessment has been considered as an important driver. Empirical support for these dimensions of the model is lacking. To quantify assessment achievements and explore emergent attitudes and beliefs about learning related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…Moreover, these tools help students to develop generic skills such as communication, lifelong learning and autonomy and a sense of community and thus forge a culture collaborative learning. The effectiveness of using self‐ and peer assessment to improve learning outcomes by offering opportunities to practise, assess and provide feedback on students’ attribute development has been demonstrated in many studies (Duers, ; Fete, Haight, Clapp, & McCollum, ; Ihm, Choi, & Roh, ; Khan, Payne, & Chahine, ; Luxton‐Reilly, ; Moore, Westwater‐Wood, & Kerry, ; Willeya & Gardnera, ). However, some authors (Monroe, ; Roberts, Jorm, Gentilcore, & Crossley, ) have highlighted issues relating to self‐ and peer assessment in terms of the accuracy of the evaluation.…”
Section: Mixed Approach: Self‐ and Peer Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, these tools help students to develop generic skills such as communication, lifelong learning and autonomy and a sense of community and thus forge a culture collaborative learning. The effectiveness of using self‐ and peer assessment to improve learning outcomes by offering opportunities to practise, assess and provide feedback on students’ attribute development has been demonstrated in many studies (Duers, ; Fete, Haight, Clapp, & McCollum, ; Ihm, Choi, & Roh, ; Khan, Payne, & Chahine, ; Luxton‐Reilly, ; Moore, Westwater‐Wood, & Kerry, ; Willeya & Gardnera, ). However, some authors (Monroe, ; Roberts, Jorm, Gentilcore, & Crossley, ) have highlighted issues relating to self‐ and peer assessment in terms of the accuracy of the evaluation.…”
Section: Mixed Approach: Self‐ and Peer Assessmentmentioning
confidence: 99%
“…;Khan, Payne, & Chahine, 2017;Luxton-Reilly, 2009;Moore, Westwater-Wood, & Kerry, 2016;Willeya & Gardnera, 2010). However, some authors(Monroe, 2016;Roberts, Jorm, Gentilcore, & Crossley, 2017) have highlighted issues relating to self-and peer assessment in terms of the accuracy of the evaluation.…”
mentioning
confidence: 99%
“…During the interviews, nearly all students said that peers had been essential in negotiating discourse, understanding expectations, and improving their work. Findings highlighting the key role of peers in developing the necessary competencies, knowledge and attitudes to engage in a variety of discursive episodes seem consistent with the literature that stresses the importance of dialogue and interactions with peers in learning contexts (Androushchak et al, 2013;Bruner, 1978;Carrell et al, 2009;De Paola & Scoppa, 2010;Epple & Romano, 2010;Moore et al, 2016;Orsmond et al, 2101;Seloni, 2012;Swain, 2001;Vygostky, 1978;Wood et al, 1976;Zappa-Hollman, 2007).…”
supporting
confidence: 79%
“…In a recent literature review, Epple & Romano (2010) concluded that the evidence in different studies left little doubt as to the effect of peers both within and outside the classroom. Furthermore, there is increasing evidence of positive peer effects in student achievement in higher education (Androushchak et al, 2013;Carrell et al, 2009;De Paola & Scoppa, 2010;Moore et al, 2016).…”
mentioning
confidence: 99%
“…Peer-assisted learning is recognised as a process of gaining knowledge from another student who is further into their training (De Silva et al 2017;McLelland et al 2013).This approach has been utilised in other fields of clinical education and healthcare, including nurse training (Brannagan et al 2013) but there is limited literature identified within the paramedic profession. Moore et al (2015), recognises the positive impact peer to peer learning has on undergraduate students and how it can drive deeper learning. This is further supported by Ytreberg & Aars (2015), who suggests that physiotherapy students who have participated in peer-assisted learning, benefited from the social aspects of this activity and also, supports the student clinician to develop in an emotionally supportive learning environment.…”
Section: Introductionmentioning
confidence: 99%